Enhancement of heat transfer in a tube with regularly-spaced helical tape swirl generators - Eiamsa-ard, Smith; Promvonge, Pongjet (My University, 2005)
Influence of helical tapes inserted in a tube on heat transfer enhancement is studied experimentally. A helical tape is inserted in the tube with a view to generating swirl flow that helps to increase the heat transfer rate of the tube. The flow rate of the tube is considered in a range of Reynolds number between 2300 and 8800. The swirling flow devices consisting of: (1) the full-length helical tape with or without a centered-rod, and (2) the regularly-spaced helical tape, are inserted in the inner tube of a concentric tube heat exchanger. Hot air is passed through the inner tube whereas cold water is flowed in the annulus. The experimental data obtained are compared with those obtained from plain tubes of published data. Experimental results confirmed that the use of helical tapes leads to a higher heat transfer rate over the plain tube. The full-length helical tape with rod provides the highest heat transfer rate about 10% better than that without rod but it increased the pressure drop. To overcome this, different free-spacing ratio (s = L s/Lh) of 0.5, 1.0, 1.5, and 2.0 were examined. It was found that the space ratio value should be about unity for Re < 4000. The regularly-spaced helical tape inserts at s = 0.5 yields the highest Nusselt number which is about 50% above the plain tube. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Heat exchanger; Heat transfer; Helical tape insert; Pressure drop; Swirl flow devices